2022
DOI: 10.1186/s40337-022-00696-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by which adverse childhood experiences, other traumas and PTSD influence the health and well-being of individuals with eating disorders throughout the life span

Abstract: Background Multiple published sources from around the world have confirmed an association between an array of adverse childhood experiences (ACEs) and other traumatic events with eating disorders (EDs) and related adverse outcomes, including higher morbidity and mortality. Methods In keeping with this Special Issue’s goals, this narrative review focuses on the ACEs pyramid and its purported mechanisms through which child maltreatment and other for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 433 publications
2
8
0
Order By: Relevance
“…There likely are many possible causal or biological mechanisms driving the observed comorbidities. For instance, environmental pathogens, such as infective agents and socially adverse as well as naturally adverse experiences, can cumulatively cause excessive inflammatory responses that can lead to or exacerbate various chronic and mental diseases (Baltrusch et al 1991; von Kanel 2012; Stuller et al 2012; Nikiphorou et al 2019; Jackson and Jabbi, 2022; Brewerton 2022). Of note, four of the top 5 most likely comorbid medical conditions were the same for bipolar disorder and MDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There likely are many possible causal or biological mechanisms driving the observed comorbidities. For instance, environmental pathogens, such as infective agents and socially adverse as well as naturally adverse experiences, can cumulatively cause excessive inflammatory responses that can lead to or exacerbate various chronic and mental diseases (Baltrusch et al 1991; von Kanel 2012; Stuller et al 2012; Nikiphorou et al 2019; Jackson and Jabbi, 2022; Brewerton 2022). Of note, four of the top 5 most likely comorbid medical conditions were the same for bipolar disorder and MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, four of the top 5 most likely comorbid medical conditions were the same for bipolar disorder and MDD. Such overlapping associations may echo shared mood disorders etiology in that psychological and environmentally adverse and stressful experiences can trigger emergent mood disorders and cardiovascular and other somatic conditions (Jabbi and Nemeroff, 2019; Baltrusch et al 1991; von Kanel, 2012; Stuller et al 2012; Nikiphorou et al 2019; Jackson and Jabbi, 2022; Brewerton, 2022). In addition, this idea aligns with a recent study showing that a history of mental stress, with and without conventional stress, was associated with a significantly increased risk for myocardial ischemia with cardiovascular events (Vaccarino et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic stress disorder (PTSD) is a common comorbid condition in eating disorder (ED) patients, occurring in up to 50% of adults admitted to residential treatment (RT) [1][2][3][4]. An abundance of data from meta-analyses, national representative samples, clinical and community samples, and case control studies, have confirmed undisputable links between traumatic events and EDs, particularly for those with binge-type features [5][6][7][8][9][10]. Evidence also supports the contention that patients with significant traumatic histories and/or PTSD have distinct clinical features, including more severe ED symptoms, more suicidality, more anxiety and depressive symptoms, more experiential avoidance, and lower mindfulness [3,4,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Dissociative disorders (DDs) and their symptoms are related to overwhelming traumatic experiences, especially during childhood, and include derealization, depersonalization, time distortions, cognitive and memory alterations (including amnesia), identity alterations, and somatic sensations (American Psychiatric Association, 2022; Dorahy et al, 2015; Ogawa et al, 1997; Simeon & Putnam, 2022). Child maltreatment (CM) of all types is highly associated with eating disorders (EDs), particularly those characterized by earlier ED onset, more binge‐purge symptoms, and greater suicidality and psychiatric comorbidity (Brewerton, 2022; Molendijk et al, 2017). CM and associated traumatic experiences are also associated with comorbid PTSD, greater severity of ED, major depression (MD), state–trait anxiety symptoms, and worse quality of life (QOL) (Brewerton et al, 2020; Brewerton et al, 2021; Scharff et al, 2019).…”
Section: Introductionmentioning
confidence: 99%